Şeyh Eyüp Sabri Kalyoncuoğlu ve Teşvikiye İsmetiliği - Dağlı, Aliosman (My University, 2017)
Türk toplumunun İslamlaşmasında ve Türk kültürünün olgunlaşmasında tasavvuf ehli karizmatik şahsiyetlerin ve tasavvufi dini grupların rolü büyüktür.

Sufist charismatic figures and sufistic groups has a nessential role on Islamızation of Turkish Society and maturation of Turkish Culture.
Keywords: dini gruplar mystic; İslam dini; religious groups; religious orders; Tarikatlar; Tasavvuf